Efficacy and Safety of Phase 1 of Very Low Energy Ketogenic Therapy (VLEKT) in Subjects with Obesity and Mild Renal Impairment - Verde, Ludovica; Barrea, Luigi; Galasso, Martina; Lucà, Stefania; Camajani, Elisabetta; Pisani, Antonio; Colao, Annamaria; Caprio, Massimiliano; Muscogiuri, Giovanna (Nutrients, 2025)
Background: Obesity impairs renal function through direct mechanisms, such as proinflammatory adipocytokine production, and indirect mechanisms, including obesity-related comorbidities. Despite the increasing prevalence of obesity and chronic kidney disease (CKD), clinical guidelines for their combined management remain lacking. Very Low Energy Ketogenic Therapy (VLEKT) has demonstrated efficacy in weight loss, but evidence on its safety and efficacy in individuals with obesity and mild renal impairment is limited. This study aimed to assess the efficacy and safety of Phase 1 of VLEKT in individuals with obesity and mild renal impairment. Methods: This cross-sectional study included 73 individuals with overweight or obesity (mean age 53.7 ± 8.8 years; BMI 35.3 ± 4.2 kg/m2) and an estimated glomerular filtration rate (eGFR) of at least 60 mL/min/1.73 m2 (evaluated using the CKD-EPI equation). Anthropometric (weight, BMI, and waist circumference) and biochemical parameters (fasting plasma glucose, insulin, cholesterol profile, triglycerides, AST, ALT, and urea) were collected at baseline and after 45 (±2) days of Phase 1 of VLEKT. Results: At baseline, 54.8% of participants had an eGFR <90 mL/min/1.73 m2, while 45.2% had an eGFR ≥ 90 mL/min/1.73 m2, with no significant differences in sex distribution. After 45 (±2) days of Phase 1 of VLEKT, both groups showed significant reductions in BMI (p < 0.001), waist circumference (p < 0.001), fasting plasma glucose (p ≤ 0.004), insulin (p < 0.001), HOMA-IR (p < 0.001), total cholesterol (p < 0.001), LDL cholesterol (p < 0.001), LDL/HDL ratio (p ≤ 0.002), triglycerides (p ≤ 0.009), AST (p ≤ 0.034), and ALT (p ≤ 0.009). Notably, the eGFR significantly increased in participants with an eGFR < 90 mL/min/1.73 m2 (p < 0.001), while no changes were observed in those with an eGFR ≥ 90 mL/min/1.73 m2. Conclusions: Phase 1 of VLEKT could effectively promote weight loss and metabolic improvements without compromising renal function, even in individuals with obesity and mild renal impairment. Further research is warranted to confirm the efficacy and safety of VLEKT and to assess outcomes across all protocol phases.